Penafsiran al-Qur’an Retoris di Media Sosial: Pola Persuasif Ustaz Adi Hidayat melalui YouTube - Ghozali, Mahbub (Jalsah : The Journal of Al-quran and As-sunnah Studies, 2022)
Technological developments in the media are used by speakers to expand the range of meaning of the Qur'an rhetorically. Meaning is presented interactively to provide an effective impact of understanding by involving persuasive tools in explanatory rhetoric. This study aims to show Adi Hidayat's persuasive mechanism on the Adi Hidayat Official YouTube Channel as the new face of Qur'an interpretation on social media. To achieve this goal, this study uses qualitative methods with content analysis as an analytical tool. The emphasis on the persuasive model in Hidayat's interpretation was identified using the rhetorical approach initiated by Aristotle. This study concluded that the effectiveness of Hidayat's expression was influenced by his appearance as a credible and authoritative figure in the meaning of the Qur'an. This method is strengthened by the selection of arguments to emphasize and strengthen the meaning given properly and legitimately. Meanwhile, the emphasis on a meaning related to law, ethics, and theology utilizes the emotions of the listener with its various functions and goals. The use of various aspects of meaning has an impact on the effectiveness of interpretation on social media dynamically and adaptively.